Implementasi Strategi Influencer Marketing untuk Membangun Brand Awareness di Industri Skincare Pria - Adireja, Muhamad Husni; Barkah, Cecep Safa’atul; Novel, Nurillah Jamil Achmawati (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The purpose of this study is to look into how influencer marketing techniques affect brand awareness in the men's skincare market. The method used is a literature review that examines relevant literature from scientific journals, using keywords such as "Advertising," "Strategy Implementation," and "Brand Awareness." Data was collected through Google Scholar and analyzed using bibliographic annotation techniques. The results show that influencer marketing has great potential to enhance brand awareness and consumer purchase intention. The appropriate use of influencers can increase public trust and brand strength, while inappropriate influencer selection can have negative impacts. The study also emphasizes that effective influencer marketing strategies involve selecting influencers that match the product persona and using integrated and sustainable marketing strategies. Thus, companies in the men's skincare industry can utilize influencer marketing to achieve optimal results in building brand awareness and encouraging consumer purchasing decisions.